Nzvi-Based Nanomaterials Used for Phosphate Removal from Aquatic Systems - Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In the last decade, the application of nanoscale zero-valent iron (nZVI) has garnered great attention as an adsorbent due to its low cost, non-toxicity, high porosity, and BET-specific surface area. In particular, the immobilization of nZVI particles onto inorganic and organic substrates (nanocomposites) decreased its agglomeration, allowing them to be effective and achieve greater adsorption of pollutants than pristine nanoparticles (NPs). Although nZVI began to be used around 2004 to remove pollutants, there are no comprehensive review studies about phosphate removal from aquatic systems to date. For this reason, this study will show different types of nZVI, pristine nZVI, and its nanocomposites, that exist on the market, how factors such as pH solution, oxygen, temperature, doses of adsorbent, initial phosphate concentration, and interferents affect phosphate adsorption capacity, and mechanisms involved in phosphate removal. We determined that nanocomposites did not always have higher phosphate adsorption than pristine nZVI particles. Moreover, phosphate can be removed by nZVI-based nanoadsorbents through electrostatic attraction, ion exchange, chemisorption, reduction, complexation, hydrogen bonding, and precipitation mechanisms. Using the partition coefficient (PC) values, we found that sepiolite-nZVI is the most effective nanoadsorbent that exists to remove phosphate from aqueous systems. We suggest future studies need to quantify the PC values for nZVI-based nanoadsorbents as well as ought to investigate their phosphate removal efficiency under natural environmental conditions. © 2023 by the authors.